Local Wisdom as the Foundation of Multicultural Education in Indonesia - Muchammad Mugiono (Yayasan Insan Mulia Bima, 2026)
Multicultural education in Indonesia often remains trapped in theoretical abstractions that are disconnected from the sociocultural realities of students. This study aims to examine local wisdom as a foundation for contextual multicultural education, identify multicultural values within various Indonesian traditions, and formulate strategies for their integration into learning processes. This research employs a systematic literature review with a qualitative-descriptive approach, analyzing data sourced from SINTA-accredited journals (2015–2025), textbooks, and conference proceedings. The findings indicate that Indonesian traditions such as Pela Gandong (Maluku), Mapalus (Minahasa), Ngayah (Bali), Ruwatan (Java), Grebeg-Sekaten (Yogyakarta-Solo), Cap Go Meh, and Lomban (Cirebon) inherently embody values of tolerance, equality, and cross-identity fraternity. Strategies for integrating such local wisdom can be implemented through formal curricula, extracurricular activities, project-based learning (PjBL), Culturally Responsive Teaching (CRT) approaches, and teacher modeling. Nevertheless, significant challenges persist in its implementation, specifically the scarcity of cultural documentation, insufficient teacher training, and the dominance of a centralized curriculum. This paper contributes to shifting the paradigm of multicultural education toward pedagogical practices rooted in local culture, while offering a practical framework for educators in the field.